Substance-Abusing Parents and Their Children from a “Family Illness” perspective: Dynamics and Treatment - Karaman, Hakan (Addicta: The Turkish Journal on Addictions, 2018)
Atıf: Karaman, H. (2018). Madde kullanan ebeveynler ve “aile hastalığı” perspektifinden çocukları: Dinamikler ve tedavi teklifleri [Review of the book Children of substance-abusing parents: Dynamics and treatment, by S. L. A. Straussner & C. H. Fewell]. Addicta: The Turkish Journal on Addictions, 5, 599‒601. http://dx.doi.org/10.15805/addicta.2018.5.3.0035R